PENGARUH PUBLIC OWNERSHIP DAN GROWTH OPPORTUNITY TERHADAP LEVERAGE DAN FUTURE EARNINGS RESPONSE COEFFICIENT - Henny, Henny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2017)
The purpose of the study to obtain empirical evidence regarding (1) The direct effect to Future Earnings Response Coefficient: (a) Public Ownership positive effect on Future Earnings Response Coefficient, (b) Growth Opportunity positive effect on Future Earnings Response Coefficient, (c) Leverage negatively affect Future Earnings Response Coefficient. (2) The indirect effect to Future Earnings Response Coefficient, through Leverage: (a) Public ownership through a leverage effect on Future Earnings Response Coefficient, (b) Growth Opportunity through a leverage effect on Future Earnings Response Coefficient. (3) The effect of direct and indirect effect that has the most significant effect on Future Earnings Response Coefficient. The method used is the Structure Equation Model (SEM) using AMOS 22, 2008-2011 with the data used from the years 2007 to 2014, bringing the total number of samples observed data 273 manufacturing companies. The results showed a variable that has a direct effect to Future Earnings Response Coefficient is variable Public Ownership, Growth Opportunity and Leverage, while the variable that most effect directly to Future Earnings Response Coefficient is variable Leverage. The variables that have an indirect effect to Future Earnings Response Coefficient through leverage is variable of Growth Opportunity, so variable of Growth Opportunity through this leverage that most have indirect effect on Future Earnings Response Coefficient.Keywords: Future Earnings Response Coefficient, Growth Opportunity, Leverage, and Public Ownership